Jurčič in sodobniki - Hladnik, Miran (Jezik in slovstvo, 2022)
The Digital Library of Slovenia enables the monitoring of mentions of writers in publications and the comparison of their appearance. It was used to investigate the place of Josip Jurčič among the storytellers of his time and examine how his name was preserved in the cultural memory after his death, thus supporting canonisation. During his lifetime, Jurčič was the most prominent storyteller, but after his death, Ivan Tavčar took over this role. Fran Levstik is also regarded as more important than Jurčič today, even though his name was virtually unknown in the nineteenth century. Together with Janez Trdina, Jurčič is more prominent than other contemporaneous storytellers, such as Luiza Pesjakova, Josip Stritar and Anton Koder. The titles of his works Deseti brat, Sosedov sin and Jurij Kozjak appeared most often in the press, but his journalistic and editorial activities anchored his name in the public consciousness more than his fiction.
Keywords: cultural memory; culturomics; Digital Library of Slovenia; Digitalna knjižnica Slovenije; Jurčič, Josip; kulturni spomin; kulturomika